IMPLIKASI PERALIHAN URUSAN PEMERINTAH DAERAH KABUPATEN/KOTA KEPADA PEMERINTAH DAERAH PROVINSI DALAM PENGUSAHAAN PERTAMBANGAN RAKYAT DI SEKTOR PERTAMBANGAN MINERAL LOGAM (EMAS) BERDASARKAN UNDANG - UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Ocy Ananda Erica; Emilda Firdaus; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
After the issuance of National Constitution 23 on 2014 about RegionalGovernment substitute for National Constitution 32 on 2004 about RegionalGovernment it has implications for changes in the authority of the management ofMinerals and Coal based on National Constitution 4 on 2009 about Minerals andCoal, problems arising from transfer of authority from Regency / City to Provinceafter the issuance of National Constitution 23 on 2014 and community miningpermits in the metal mineral (gold) mining sector which is still a polemic of theProvincial Government in carrying out its duties so that disharmony occursbetween the two laws.The purpose of this thesis is to find out the regulation of metal mineralgold mining under National Constitution 23 on 2014 about Regional Governmentto find out the implications of the transition of Regency / City RegionalGovernment affairs to Provincial Governments in the exploitation of communitymining in the metal mineral mining sector (gold) based on National Constitution23 on 2014 about Regional Government.the regulation of mining business was not in accordance with the laws andregulations that governed previously, namely the mining permit so that legaldisharmony occurred between the two laws, the difference being related to theauthority to grant mining permits in the province or district / the city thusinconsistencies towards the dualism of the same law. As well as the transitionalimplications, it requires the Provincial Government to be able to accommodatemining licenses with uncomplicated bureaucracy with the existence of derivativeregulations from National Constitution 23 on 2014 about Regional Government.Keywords: Regional Government, People's Mining, Metal Minerals (Gold)